Estimation of Cynogenic Content in Edible Bamboo Shoots through Picrate Paper Method - Singh, Pankaj; Das, Rameshwar; Singh, Sanjay; Kumari, Priya (Indian Forester, 2014)
Bamboo shoots are delicious, taste sweet, rich in carbohydrate, protein, vitamin and essential amino acids. Despite these nutrtious quality, bamboo shoots have cynogenic glycosides which releases hydrocyanic acid (HCN) on hydrolysis. Picrate paper method was found convinient and reliable protocol to estimate hydrocyanic acid content in edible bamboo shoots. Present study was done on edible shoots of three bamboo including B. tulda and D. strictus and found that tender shoots of B. tulda are edible and good for human health as it has lower content of hydrocyanic acid. Overall middle part of the shoots contained maximum amount of HCN content in all species.